2012
DOI: 10.2174/1874312901206010054
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Test Abnormalities are Common in Polymyositis and Dermatomyositis and Differ Among Clinical and Demographic Groups

Abstract: Objective:Given the difficulties regarding the interpretation of common laboratory test results in polymyositis (PM) and dermatomyositis (DM) in clinical practice, we assessed their range of abnormalities, differences among phenotypes and interrelationships in a large referral population.Methods:We retrospectively assessed 20 commonly measured blood laboratory tests in 620 well-defined PM/DM patients at different stages of illness and treatment to determine the frequency, range of abnormalities and correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 26 publications
7
37
0
3
Order By: Relevance
“…CRD is 1 type of spontaneous potential and occurs in 25% of patients with PM. These results were similar to those previously reported 16 with the exception of CRDs, which occurred less frequently (6.45%) than reported. 17 We found that prolonged insert potential occurred in 15.88% of muscles, and spontaneous potential occurred in 68.8% of muscles.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…CRD is 1 type of spontaneous potential and occurs in 25% of patients with PM. These results were similar to those previously reported 16 with the exception of CRDs, which occurred less frequently (6.45%) than reported. 17 We found that prolonged insert potential occurred in 15.88% of muscles, and spontaneous potential occurred in 68.8% of muscles.…”
Section: Discussionsupporting
confidence: 93%
“…16 Fasciculation potential was previously reported in 10% of cases. CRD is 1 type of spontaneous potential and occurs in 25% of patients with PM.…”
Section: Discussionmentioning
confidence: 97%
“…5 Transaminases catalyze the transfer of an amino group from an amino acid to a keto acid 2 and are found predominantly in the liver and at smaller concentrations in skeletal muscle, myocardium, kidney, pancreas, lung, spleen, and red blood cells. 6,7 Of note, a retrospective analysis of 61 myositis patients demonstrated a linear relationship between log serum CK and log ALT (r = 0.78, r 2 = 0.59, P G 0.001) 6 and reported that the ALT level can be predicted based on the rise in CK. This Previous studies have shown a positive correlation between levels of CK and ALT.…”
Section: Discussionmentioning
confidence: 99%
“…For muscle enzymes, the most abnormal enzyme at baseline is used. The enzyme range was calculated based on 90% range of enzymes from natural history data (5;36), and for creatine kinase is 15 times the upper limit of normal; for aldolase is six times the upper limit of normal, and for lactate dehydrogenase, aspartate aminotransferase, and alanine aminotransferase is three times the upper limit of normal. An Improvement Score is assigned for each core set measure based on the absolute percent change.…”
Section: Tablementioning
confidence: 99%